Testing the Psychology of Working Theory Among Economically Marginalized Workers - (:unkn) unknown (My University, 2022)
ABSTRACT TESTING THE PSYCHOLOGY OF WORKING THEORY AMONG ECONOMICALLY MARGINALIZED WORKERS byWilly Anthony Diaz Tapia The University of Wisconsin-Milwaukee, 2022 Under the Supervision of Professor Kelsey Autin In 2018, the U.S. Census Bureau estimated that approximately 39.7 million U.S. Americans lived in poverty of which 6.9 million were considered the working poor. People from economically marginalized communities experience significant challenges in many areas of life and work is no exception; yet their work lives continue to be underrepresented in vocational literature. The Psychology of Working Theory (PWT) is one of the first vocational theories developed explicitly to better understand and support communities that experience marginalization and economic constraints, but it has yet to be tested among economically marginalized communities. This study is the first known examination to test PWT propositions among a sample representative of economically marginalized workers. Through conducting this study, I sought to answer two questions by testing 14 PWT propositions (see Figure 2 for hypothesized paths): (1) do contextual factors (i.e., economic constraints and marginalization) impact a person’s ability to secure decent work; and (2) does career adaptability and work volition mediate the relation from contextual barriers to attainment of decent work? I used structural equation modeling (SEM) to examine the 14 PWT propositions. Results generally supported PWT propositions and suggest that it is applicable and culturally attuned to the experiences of economically marginalized workers. Practical implications were discussed.
Keywords: career adaptability; decent work; economic constraints; marginalization; poverty; Psychology of Working Theory